A comparison of arsenic exposure in young children and home water arsenic in two rural West Texas communities - Michelle Del Rio; Juan Alvarez; Tania Mayorga; Salvador Dominguez; Christina Sobin (BMC, 2017)
Abstract Background In a previously conducted Health Impact Assessment of a well-water dependent southwest community, arsenic (As) levels greater than the EPA Maximum Contaminant Level (10 μg/L) were identified in home water samples. The goals of this study were to test whether children from the previously studied well-water dependent community (Community 1) had higher blood As levels than children from a demographically similar and geographically nearby community dependent on a municipal water supply (Community 2); to test whether home water As levels predicted child As blood levels; and to examine how child As blood levels changed over time. Methods This was an observational study of 252 children aged 4 to 12 years from two communities. Children were recruited through elementary schools and tested during the school day; 204 children participated in follow-up testing. Home water samples were collected according to U.S. Environmental Protection agency recommended procedures. Child heavy metal blood levels and home water sample heavy metal levels were analyzed using inductively coupled plasma mass spectrometry. General linear regression analysis was used to test the influence of community on child As levels, and to examine the contribution of home water As levels to child blood As levels. Results Arsenic was detectable in all children tested. Blood levels ranged from 0.09-2.61 μg/dL; approximately 31% of children tested at Time I (79/252) had blood As values above the current acceptable limit (1.2 μg/dL). Approximately 8% of household water samples (6/76) had As levels higher than 10 μg/L. Community did not predict child blood As levels; seasonal effects differed by Community. At Time II, child blood As levels were higher in Community 2 than in Community 1. Conclusion A large proportion of children in the communities tested had As exposure. Home water As levels did not predict child blood As levels. Fluctuating child blood As levels by season and over time suggested the contribution of multiple factors and the need for further studies.